The Function and Role of Money: Analysis in Islamic Economic Studies as a Unit of Value and as a Medium of Exchange - Fitria Marisya; R.A Rodia Fitri Indriani; Marsinah Marsinah (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
In Islamic economic studies, there are only 2 functions of money: money as a unit of value and money as a medium of exchange. There are four functions of money in the conventional economic system: money as a unit of calculation, money as a unit of exchange, but in conventional principles, money not only functions as a legal medium of exchange but also as goods that can be traded or to get profits, money as a unit of store of value, and money as a standard unit of payment in the future. This study aims to find out how the people of Bukittinggi perceive the function of money from an Islamic economic perspective. The type of research used is qualitative descriptive research. The research informant was the Muslim community of Bandar Lampung City. Collecting data is done through documentation, observation, and interviews. The data analysis techniques used are data reduction, data presentation, and conclusions. From the results of research conducted by researchers, it was found that most people's perceptions about the function of money are in line with Islamic economics, but a small number have perceptions that are not in line with Islamic economics because they think that money can be used as a tool to take personal advantage. This is contrary to the concept and function of money in Islam